Redox Role of Lactobacillus casei Shirota Against the Cellular Damage Induced by 2,2′-Azobis (2-Amidinopropane) Dihydrochloride-Induced Oxidative and Inflammatory Stress in Enterocytes-Like Epithelial Cells - Finamore, Alberto; Ambra, Roberto; Nobili, Fabio; Garaguso, Ivana; Raguzzini, Anna; Serafini, Mauro (Frontiers in Immunology, 2018)
In western societies where most of the day is spent in the postprandial state, the existence of oxidative and inflammatory stress conditions makes postprandial stress an important factor involved in the development of cardiovascular risk factors. A large body of evidence have been accumulated on the anti-inflammatory effects of probiotics, but no information is available on the mechanisms through which intestinal microbiota modulates redox unbalance associated with inflammatory stress. Here, we aimed to investigate the ability of Lactobacillus casei Shirota (LS) to induce an antioxidant response to counteract oxidative and inflammatory stress in an in vitro model of enterocytes. Our results show that pretreatment of enterocytes with LS prevents membrane barrier disruption and cellular reactive oxygen species (ROS) accumulation inside the cells, modulates the expression of the gastro-intestinal glutathione peroxidase (GPX2) antioxidant enzyme, and reduces p65 phosphorylation, supporting the involvement of the Nfr2 and nuclear factor kappa B pathways in the activation of antioxidant cellular defenses by probiotics. These results suggest, for the first time, a redox mechanism by LS in protecting intestinal cells from AAPH-induced oxidative and inflammatory stress.